Astrophotography as a Medium for Affective Sustainability Communication in Alternative Tourism: A Qualitative Study Using Photo Elicitation - Adhika Graha Irianto Putra; Bambang Hermanto; Yunus Winoto; Evi Novianti; Yosa Fiandra (INJECT (Interdisciplinary Journal of Communication), 2025)
Sustainability communication in the tourism sector often faces challenges in fostering substantial public engagement, primarily due to a reliance on overly rational and academic approaches. This study aims to address this gap by exploring the potential of astrophotography as an effective visual communication medium for conveying sustainability values. Employing a qualitative approach, specifically through photo elicitation and a visual hermeneutics framework, this research analyzes how audiences interpret astrophotography images and the impact of these interpretations on their perceptions of environmental issues. The findings indicate that night sky imagery effectively elicits profound affective responses, such as experiences of transcendence, contemplation, and nostalgia. These responses contribute directly to an increased ecological awareness and a greater appreciation for preserving the night sky from light pollution. The study's findings affirm that astrophotography can function as a powerful visual bridge, connecting aesthetic beauty with the urgency of environmental conservation. This research not only enriches the visual communication literature but also provides a practical foundation for tourism stakeholders to leverage astrophotography as an effective tool for promoting responsible tourism and enhancing environmental awareness.